Ultra-Sensitive Nanoplatform for Detection of Brain-Derived Neurotrophic Factor Using Silica-Coated Gold Nanoparticles with Enzyme-Formed Quantum Dots - Seona Yu; Jaewon Choi; Yu-Rim Ahn; Minse Kim; Nanhyeon Kim; Hwunjae Lee; Hyun-Ouk Kim (Molecules)
A fluorescence-based detection platform was developed for brain-derived neurotrophic factor (BDNF), a key biomarker of Alzheimer’s disease (AD). This platform utilizes localized surface plasmon resonance effects resulting from the interactions between silica-coated gold nanoparticles (Au@SiO2) and enzymatically synthesized quantum dots (QDs). The gold nanoparticles were silica coated via the hydrolysis of tetraethyl orthosilicate, which allowed for precise control over the distance between the nanoparticles and QDs and refined the dynamics of fluorescence quenching and enhancement. Antibody conjugation was performed via sequential amination and carboxylation, followed by EDC/NHS coupling. BDNF was detected across a range of concentrations, from 1 ng/mL to 1 ng/mL, using an alkaline phosphatase (ALP)-conjugated polyclonal antibody targeting a secondary epitope of BDNF. The enzymatic hydrolysis of p-nitrophenyl phosphate by immobilized ALP led to the formation of cadmium sulfide QDs, with the fluorescence intensity correlating directly with the BDNF concentration. This platform offers a refined and precise method for detecting BDNF and is a reliable tool for the early diagnosis of AD.